The Banning of Extremist Political Parties as a Measures of Neo-militant Democracy: The Experience of Post-communist States - Skrzypek, Maciej (HAPSc Policy Briefs Series, 2020)
The paper aims to determine which political parties in post-communist countries were considered hostile to the system and evaluate the systems’ capacity to eliminate their enemies with political party banning. The analysis overs Bulgaria, Czech Republic, Estonia, Lithuania, Latvia, Poland, Romania, Slovakia, and Hungary. The study covers the period from their democratization to 2020.